Vocational rehabilitation for people with multiple sclerosis: A systematic scoping review of international evidence - Carlotta Gualco; Erica Grange; Federica Rotondi; Marco Salivetto; Elena Pignattelli; Tommaso Manacorda; Maria Grazia Grasso; Giorgia Presicce; Matilde Inglese; Lorenza Nasone; Paolo Durando; Guglielmo Dini; et al. (PLoS ONE, 2026)
Introduction People with multiple sclerosis (pwMS) may encounter challenges in their professional lives, due to a combination of environmental and individual factors. According to Escorpizo et al., 2011 framework, Vocational rehabilitation (VR) aims to optimise job participation, providing support in the job access, retention and in the return to work for people with disability. However, the corpus of research on VR for pwMS is poor. This scoping review aims to map the available literature on VR interventions for pwMS, summarising their characteristics, study designs, implementation features, feasibility, and stakeholders’ perspectives. Methods Following the Joanna Briggs Institute (JBI) and the PRISMA-ScR guidelines, seven databases were searched up to October 2025: PubMed, SCOPUS, PsycInfo, CINAHL, Google Scholar, OT Seeker (University of Queensland), and the Physiotherapy Evidence Database (PEDro). Studies were eligible if they were related to VR interventions for pwMS, focused on job access, return, or retention and if they were primary articles. Data were extracted and synthesised following the Population–Concept–Context (PCC) framework. Results Out of 2,360 records, 28 articles describing 28 distinct VR interventions were included. Studies were published between 1996 and 2025, mostly from Western countries. Designs ranged from descriptive to randomized trials, with an increasing number of interventional and feasibility studies in recent years. The 61% of the interventions were multi-dimensional delivering a combination of rehabilitation, educational, and reasonable accommodation services. PwMS highlighted the importance of empathetic and individualized approaches, symptom management, and legal counselling as key elements in VR interventions, while logistical, personal and health issues were barriers to participation. Overall, interventions were considered feasible and acceptable. Conclusions This is the first comprehensive overview of VR interventions for pwMS, outlining a progressive shift toward multidisciplinary and goal-oriented approaches over time. Despite promising feasibility and stakeholder satisfaction, further rigorous trials are needed to evaluate effectiveness and inform evidence-based implementation of VR programmes in diverse contexts.